Improving Light-Load Efficiency by Eliminating Interaction Effect in the Grid Connected Doubly-Fed Induction Generator - Seyed Esmaeel Mirhosseini Niri; Abdolhossain Tahani; Mohammad Yazdani-Asrami; S. Asghar Gholamian (Institute of Advanced Engineering and Science, 2014)
A wind turbine equipped with doubly-fed induction generator (DFIG) is used in wind power plant industry. This paper studies the maximum power extraction of DFIG via evaluation of state-space equations in closed loop control condition for improving light-load efficiency. The DFIG state-space equations have been considered in the form of a multi-input- multi output (MIMO) system. Also, the tracing table has been used to determine the speed which the generated power will be proportional to the maximum load. The tracing table input is the generator speed, and its output is the optimum active power that has been considered as the reference power of the active power control system of the convertor. A controller is presented for the tracing table and the extracted power is able to follow the reference power with minimum ripple. Then, the results are compared with the single-input and single-output (SISO) case, for the values up to 0.2 times of the rated load. Therefore, in MIMO modeling, in the case that the DFIG connected to the grid, by eliminating the interaction effect, the efficiency in light-load can be increased.